THE ASSESMENT OF THE PHYSICAL FITNESS ON MENTALLY RETARDED CHILDREN - Necmiye Ün; Fatih Erbahçeci; Nevin Ergun (Archives of Rheumatology, 2001)
This study designed to measure physical fitness on trainable mentally retarded children who do any kind of sports and those who don’t along with healty ones; and also to find out the effect of sports on physical fitness has been carried out in A.İ.B.Ü. K. Demir Physical Therapy and Rehabilitation, Ulus Anadolu Practical-Training School, Gölbaşı Procting and Caring Trust of Mentally Retarded Children- Among the Subject Scovered by the study there were 20 nonretarded (I. Group), 20 trainable mentally retarded who don’t do sports (II. Group), 20 trainable mentally retarded who do sports (III.Group). The avarage ages of subjects were determined as a 15,35 ± 0,21 years in group I, 15,00 ± 0,22 years in group II, 15,15 ± 0,21 years group III. Physical structure and physical fitness of both nonretarded and mentally retarded children were evaluated. A statistically important difference was found in all physical fitness parameters except cardiovasculer endurance, body composition and pulling one’s body up with arms parameters. (p<0,05). As a result, it has been concluded that sport is a valid and effective means of training which improves the levels of physical fitness and independence in activities of daily living of mentally retarded children.